Urban land tenure and property rights in developing countries - Payne, Geoffrey (London, 1997)
This review surveys the extensive international literature on the subject. It proposes a typology which includes statutory, customary and unauthorized tenure systems, as a basis for assessing existing problems and formulating appropriate policies. It concludes with recommendations for improving tenure security which maximize benefits to the poor and minimize market distortion.
Keywords: Land reform Urban